Penguatan Etika Pembelajaran Deep Learning Perspektif Hadis Pada Kitab Al-Targhib Wa Al-Tarhib; Tinjauan Metodologi Kritik Hadis Musahadi HAM - Fitratul Uyun; Muhammad Walid; Sarkowi Sarkowi; Triyo Supriyatno; Ahmad Barizi (J-PAI: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the sanad validity and to develop a contextual interpretation of a prophetic tradition on learning narrated by Abu Hurayrah and recorded in al-Tirmidzi's Sunan (Kitāb al-Zuhd). Textually, the hadith may give rise to interpretive ambiguity and appears to be in tension with Qur’anic principles and other prophetic traditions concerning the relationship between worldly life and knowledge. This research employs a library-based qualitative method using Musahadi HAM’s hadith-criticism approach, which integrates sanad criticism, matn criticism, and maqāṣid-based contextualization through historical, eidetic, and practical analyses. The findings indicate that the hadith is classified as ṣaḥīḥ and maqbul, despite its status as an āḥād gharīb narration. Eidetic analysis reveals that the hadith does not constitute a total condemnation of the world; rather, it represents a universal critique of materialistic life orientations detached from divine values. The explicit exception granted to scholars (‘ālim) and learners (muta‘allim) affirms that knowledge and the process of learning constitute the ethical foundation that renders worldly life meaningful and enables social transformation. In the context of contemporary education, this hadith provides an ethical framework for deep, meaningful, and transformative learning, resonating with the paradigm of deep learning that emphasizes internalization of values, character formation, and moral transformation.